A Characterization of Uniform Well Posedness for Degenerate Second-Order Abstract Differential Equations - Lizama-Yanez, C (Birkhauser, 2023)
We completely characterize the uniform well-posedness of the Dirichlet boundary value problem for degenerate second order abstract differential equations in Hilbert and Banach spaces. Our characterization is given solely in terms of spectral properties of the data and uniform boundedness properties of an appropriate resolvent operator. © 2023, The Author(s), under exclusive licence to Springer Nature Switzerland AG.